Room-temperature synthesis of Fe3O4/Fe-carbon nanocomposites with Fe-carbon double conductive network as supercapacitor. (10th October 2016) - Sun, Jinkun; Zan, Ping; Yang, Xijia; Ye, Lin; Zhao, LiJun
Graphical abstract: Double conductive network of Fe-carbon nanotubes (CNTs) stimulates the capacitive performance of Fe3O4, leading to great improvement of specific capacitance of Fe3O4/Fe-CNTs nanocomposites. Abstract: Here, we report a new strategy to fabricate unique Fe3 O4 /Fe-carbon nanotubes (CNTs) nanocomposites at room temperature by a facile chemical synthesis method. In this ternary complex, CNTs were linked and coated by catenulate Fe3 O4 /Fe particles and were able to form conductive networks, which could reduce interfacial resistance between the electrode and electrolyte, improving the ions diffusion. Compared with single Fe3 O4, discharge times of Fe3 O4 /Fe-CNTs nanocomposites were improved twentyfold. The Fe3 O4 /Fe-CNTs nanocomposites show a high specific capacitance of 1065 F g −1 at current density of 1 A g −1 and cycle stability with 82.1% retention of its initial specific capacitance at 1 A g −1 after 1000 cycles, which is better than most of Fe3 O4 systems reported previously.